KARAKTER NEGATIF MANUSIA DALAM AL-QURAN - Otong Surasman (Universitas PTIQ Jakarta, 2021)
This research is an attempt to provide a description of the negative human character, through studies sourced from the holy book of the Al-Qur'an, because in general many humans are unable to describe the absolute truth. In fact, there is confusing information and various kinds of arguments used to legalize what is haram are allowed for humanitarian reasons. Whereas something that is forbidden by the teachings of Islam, of course, has a lot of negativity, and on the contrary, what is legal must provide more benefits for human life. This study aims to identify the negative character of humans, so that humans avoid themselves from these negative characters, so that they will be free from the ugliness that will befall them both in this world, especially in the afterlife. In this study, the authors used a thematic interpretation method, trying to collect verses from the Al-Qur'an, which were related to the negative character of humans. A temporary conclusion, by not knowing the negative character of humans, it is likely that human life will not find peace in their lives.